Mortality Trends in the United States due to Concurrent Heart Failure, Atrial Fibrillation/Flutter and Sepsis - Shanmuganathan, Gaithrri; Lee, Nicole Jeongha; Agrawal, Devendra K (Cardiology and Cardiovascular Medicine, 2026)
Heart failure (HF), atrial fibrillation (AF)/atrial flutter (AFL) and sepsis commonly co-occur in hospitalized patients. This study determines temporal mortality trends associated with concurrent HF, AF/AFL, and sepsis among adults across demographic and geographic groups in the United States. The CDC Wonder database was utilized to extract age-adjusted mortality rates (AAMR) per 100,000 for deaths listing HF, AF/AFL, and sepsis. Trends were analyzed by age, race/ethnicity, region, and sex. Joinpoint regression calculated the annual percent change (APC) and average annual percent change (AAPC) for AAMR with 95% CI. From 1999 to 2023, there were 1,749,565 deaths involving HF, AF/AFL, and sepsis. AAMR doubled (1999: 11.79 vs. 2020: 23.87 per 100,000), with a critical 2012 inflection point accelerating mortality from 1.29% to 6.42% annually. White individuals had steepest post-2012 acceleration (6.67%), surpassing Black individuals by 2020 (24.88 vs. 20.80 per 100,000). Males had higher AAMRs than females (28.69 vs 20.19 per 100,000 in 2020). Middle-aged adults (45-64 years) showed highest acceleration (9.98-10.30%), nearly double those aged ≥85 years (5.82%). The Midwest and South had steepest increases (7.07% and 7.11%). During 2018–2023, mortality continued increasing at 6.11% annually without stabilization. Mortality involving HF, AF/AFL and sepsis doubled from 1999–2023 with sustained acceleration and no post-pandemic stabilization. Targeted interventions should focus on males, middle-aged adults, and high-risk regions with enhanced post-discharge care.